2021
DOI: 10.22271/j.ento.2021.v9.i1d.8156
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal incidence of yellow stem borer, Scirpophaga incertulas Walker infesting rice and its correlation with weather parameters

Abstract: The present investigation was conducted to study the seasonal incidence of yellow stem borer, Scirpophaga incertulas Walker infesting rice and its correlation with weather parameters at MAE farm, Regional Agriculture Research Station, Karjat (M.S.), during Kharif 2019. Results revealed that intiation of yellow stem borer infestation was observed with (3.06%) dead heart, (1.72%) white ears head during the 31 st SMW (30 July -5 Aug) and 40 th SMW (1Oct -7 Oct) respectively. The maximum dead heart was recorded wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
4
2
0
Order By: Relevance
“…It was observed that R 2 = 82.50; which indicated that weather parameters together were responsible for 82.50% fluctuation in the H. armigera population in 2020-21. The results of the present study were in similar trend with the previous study conducted by Wade et al (2020) who reported fruit borer had non-significant positive relation with maximum temperature (r = 0.314), positive non-significant correlation (r = 0.450) with minimum temperature and non-significant negative correlation (r = -0.484) of maximum relative humidity. However, fruit borer population recorded positive non-significant correlation with evening relative humidity (r = 0.407).…”
Section: Multiple Regressions Of Different Meteorological Parameters ...supporting
confidence: 91%
See 1 more Smart Citation
“…It was observed that R 2 = 82.50; which indicated that weather parameters together were responsible for 82.50% fluctuation in the H. armigera population in 2020-21. The results of the present study were in similar trend with the previous study conducted by Wade et al (2020) who reported fruit borer had non-significant positive relation with maximum temperature (r = 0.314), positive non-significant correlation (r = 0.450) with minimum temperature and non-significant negative correlation (r = -0.484) of maximum relative humidity. However, fruit borer population recorded positive non-significant correlation with evening relative humidity (r = 0.407).…”
Section: Multiple Regressions Of Different Meteorological Parameters ...supporting
confidence: 91%
“…After that, the population grew and peaked at the 10 th SMW. Our findings also aligned with those of Wade et al (2020), who noted the fruit borer's first incidence on the 5 th SMW; Reddy and Kumar (2004), who noted the highest incidence of Helicoverpa armigera from March to April; Kharpuse and Bajpai (2006), who reported a fruit borer population during the 3 rd week of February during Rabi, 2004Rabi, -2005Reddy et al (2009) and Pandey et al (2012), who also noted the fruit borer's peak population in March.…”
Section: Seasonal Incidence Of Major Insect Pests Of Tomatosupporting
confidence: 88%
“…These findings are similar with the finding of Sulagitti et al [17] who observed the incidence of YSB at 31 st SMW and its peak incidence at 41 th SMW. These finding also similar to Patel and Singh [18] reported the incidence of YSB first appeared at 32 nd SMW and white ear head reached peak in 45 th SMW.…”
Section: Rice Yellow Stem Borer (S Incertulas)supporting
confidence: 89%
“…They all reported that H. armigera had been a major insect pest of tomato. [18] who reported non-significant negative correlation between larval population and relative humidity morning and relative humidity evening. Singh [21] showed that maximum temperature and minimum temperature exhibited positive and significant impact on enhancing the larval population build up.…”
Section: Fruit Borer Helicoverpa Armigeramentioning
confidence: 97%
“…Present findings are partially in accordance with the Chakraborty [17] who reported that aphid population was significantly positive correlated with maximum temperature and minimum temperature whereas morning relative humidity was significantly negative correlated and rainfall was positively nonsignificant correlated. Wade et al [18] reported nonsignificant negative correlation between relative humidity and pest population, Kachave et al [9] reported that maximum temperature was positively correlated and morning relative humidity was negatively correlated with the pest population whereas non-significant role of rainfall on pest population.…”
Section: Aphid (Aphis Gossypii Glover)mentioning
confidence: 99%